Three-week topical treatment with placenta-derived mesenchymal stem cells hydrogel in a patient with diabetic foot ulcer: A case report. Issue 51 (December 2017) - Zeng, Xiangxia; Tang, Yunliang; Hu, Kaixiang; Jiao, Wang; Ying, Liu; Zhu, Lingyan; Liu, Jianying; Xu, Jixiong
Abstract: Rationale: Diabetic foot ulcer (DFU) is a chronic complication of diabetes characterized by continuity, repeatability, and nonhealing. In recent years, mesenchymal stem cells hydrogel complex has been a new emerging technique in the treatment of DFU. The placenta-derived mesenchymal stem cells (PDMSCs) hydrogel is multipotent, and can secrete growth factors, cytokines, and immunomodulatory substances which could accelerate wound healing. Patient concerns: In this case report, we present a 57-year-old female with type 2 diabetes mellitus and a 20-day DFU.A wound bed located at the dorsalis pedis of the right foot, and conventional therapies had no effect on the foot. Diagnoses: The patient was confirmed a diagnosis of type 2 DM with diabetic foot (Wagner classification III). Interventions: To assess the efficacy and safety of PDMSCs hydrogel in wound repair and to improve the rate of wound healing, we administered PDMSCs hydrogel (cell number: 1 × 10 6 /cells/cm 2 ) topically into the wound with the patient's permission. Outcomes: The patient's foot ulcer was almost healed, and foot function in walking was well preserved. No complications were observed. No recurrence occurred in the subsequent 6 months. Lessons: To the best of our knowledge, this is the first patient globally to receive PDMSCs hydrogel to treat DFU. The present case study suggests that PDMSCs hydrogel may provide a new approach to DFU treatment. Clinical Trial Registration-URL:http://www.chictr.org.cn/searchproj.aspx:chiCRT-ONC-16008732 .